Aplikasi Ekstrak Hasil Fermentasi Biji Jagung dan Rebung untuk Meningkatkan Mutu Buah Anggur Bali (Vitis vinifera L. var. Alphonso Lavallee) - I NYOMAN GEDE ASTAWA; RINDANG DWIYANI; NI NYOMAN ARI MAYADEWI; I MADE SUKEWIJAYA (Fakultas Pertanian Universitas Udayana, 2016)
Applications of Extracts of Fermented Immature Corn Seed and BambooSprout For Improvement of Table grape Quality of Vitis vinifera L. var.Alphonso Lavallee. The objective of the research was to determine the effect ofapplication of extracts of fermented immature corn seed and bamboo sprout for improvementof table grape quality. The research was designed as Completely Randomized Block Design,with five treatments and ten replications. The treatments were K0 (control), J50 (extract offermented immature seed of corn with concentration of 50%)), J100 (extract of fermentedimmature seed of corn with concentration of 100%), R50 (extract of fermented bamboo sproutwith concentration of 50%) and R100 (extract of fermented bamboo sprout with concentrationof 100%). The results showed that all of the treatments improved sugar content of the fruit.However, the treatment of J100 resulted in the greatest increase of berry number per-bunchand the lowest number of seed per-berry. In conclusion, for improvement of the table grapequality, the treatment of J100 was the most appropriate among other treatments used in thecurrent research.